RESEARCH OF THE KAZAKH-CHINESE RELATIONS (International relations and international law Journal, 2016)
In this article analyzed Kazakhstan–China relationship of Kazakhstan which basined on historical researches. Author compared with two different countries relation, according to the researched work of native land science fi eld of Soviet Union and independent period have proved our country’s science researches is developed .
Keywords: foreign policy; Kazakh-Chinese relations